Knot on her life - Marks, Mary (Marks, Mary. Quilting mystery., 2019)
While quilter Martha Rose awaits the birth of her granddaughter, a neighborhood girl appears at her door with a mystery that can<U+2019>t be pinned down . . . Martha<U+2019>s eager to finish the baby quilt she<U+2019>s making for her new granddaughter, but she scraps those plans when a young girl rings her doorbell begging for help. Poppy Halaby, the foster child of Martha<U+2019>s neighbor, is an orphan whose parents were murdered by a killer who was never caught. When Poppy<U+2019>s doting foster mom falls suspiciously ill, Martha is determined to keep the child safe. But she<U+2019>ll have to unravel more about Poppy<U+2019>s parents to stitch a broken family back together again<U+2014>and prevent another crime cut from the same cloth . . .